Predicting vaccine hesitancy among parents towards COVID-19 vaccination for their children in Singapore - Low, Jia Ming; Soo, Chloe Wen Ting; Phuong, TA; Zhong, Youjia; Lee, Le Ye (Frontiers in Pediatrics, 2022)
Background There was a considerably slower uptake among children despite the high COVID-19 vaccination uptake amongst adults and adolescents in Singapore. This was concerning as unvaccinated children are at risk of severe COVID-19 infections and a source and reservoir of infections. We sought to understand the impact of social media on parental vaccine hesitancy and to determine the risk factors associated with vaccine hesitancy. Methods An electronic survey conducted from November 2021 to March 2022. Data on the demographic profiles of respondents and to classify them based on their vaccine hesitancy status. Data including the choice of social media used to obtain information on the COVID-19 pandemic, frequency of use were collected. Statistical significance was defined as p < 0.05. Results Six hundred and twenty-eight parents participated. 66.9% of parents were not vaccine hesitant. About a third (27.2%) considered themselves somewhat vaccine hesitant. Fathers were more vaccine hesitant than mothers. Vaccine hesitancy was also associated with having a lower household income, unvaccinated parents, knowing someone with an adverse reaction to the Covid 19 vaccine and having a low level of trust in their child's doctor. There was no significant difference with high usage of social media between parents who were not vaccine hesitant vs. those who were vaccine hesitant. Despite high usage of social media, about two thirds (62.7%) of parents preferred print material to obtain COVID-19 related information. Parental trust in their child's doctor was the most significant factor in determining vaccine hesitancy amongst parents. When the variables of gender, household income status, vaccine status were further analysed with a multinomial logistic regression model, vaccine hesitancy in a parent could be predicted with a 70% accuracy, and non-vaccine hesitancy with a 92.4% accuracy. Conclusion Newspapers and print media were the primary sources used in obtaining information on COVID-19 vaccine safety and efficacy, especially amongst parents with a higher household income. Healthcare providers should continue to establish rapport amongst parents, in particular the group with a lower household income to encourage higher paediatric COVID-19 vaccine uptake as well as correct COVID-19 related vaccine misconceptions or vaccine hesitancy, if present.